2012
DOI: 10.1111/j.1460-2695.2012.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fatigue damage on static and dynamic tensile behaviour of electro‐discharge machined Ti‐6Al‐4V

Abstract: The fatigue performance of electro-discharge machined Ti-6Al-4V and, more specifically, the effect of cyclic damage on the static and dynamic tensile properties of the material have been investigated. In a first step, fatigue failure was studied. Afterwards, tensile tests were performed on specimens that had been previously subjected to cyclic loading during predefined fractions of the fatigue life. In addition to conventional experiments at quasi-static strain rate, dynamic tests were performed using a split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It is necessary to remove it to reveal the CM surface, which is representative of surface conditions of the real cast component. EDM is a process very harmful for fatigue strength of cast Ti‐6Al‐4V alloy as illustrated by Lόpez et al .…”
Section: A Representative Fatigue Specimenmentioning
confidence: 99%
“…It is necessary to remove it to reveal the CM surface, which is representative of surface conditions of the real cast component. EDM is a process very harmful for fatigue strength of cast Ti‐6Al‐4V alloy as illustrated by Lόpez et al .…”
Section: A Representative Fatigue Specimenmentioning
confidence: 99%
“…This result is consistent with the yields reported in Ref. , where fatigue tests were performed on electro‐discharge machined samples of Ti‐6Al‐4V. It was shown that the fatigue response of Ti‐6Al‐4V, as well as that of steels, is highly sensitive to the surface finishing condition.…”
Section: Preliminary Discussionmentioning
confidence: 99%
“…The rationale for selecting the surface finish as a response is its dominant importance in governing the final quality of the machined specimen [13]. Several properties like corrosion, wear and fatigue resistance are mainly governed by the level of surface finish [14]. Therefore, surface roughness (R a ) has been selected as the response characteristic.…”
Section: Introductionmentioning
confidence: 99%